Editorial - Kulkarni, Sushma S. (Journal of Engineering Education Transformations, 2019)
The â€œfourth industrial revolutionâ€ also called as â€œIndustry 4.0â€ is transforming a wide range of industrial sectors by automation with AI and machine learning , planning and construction of Smart Cities, Protection of Environment ,Internet of Things / Cloud Based Technology, Virtual offices, E-commerce and digital banking revolution.This will create an increased technical and organizational complexity of industrial processes and therefore an increase in demand for qualified staff at all organizational levels specifically engineers.